1995
DOI: 10.1093/jxb/46.special_issue.1335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and atmospheric carbon dioxide enrichment on photosynthesis and carbon partitioning in the leaves of tomato (Lycopersicon esculentum L.) plants over-expressing sucrose phosphate synthase

Abstract: Photosynthetic carbon assimilation, carbon partitioning and foliar carbon budgets were measured in the leaves of transformed tomato plants expressing a maize sucrose-phosphate synthase (SPS) gene in addition to the native enzyme, and in untransformed controls. The maize SPS gene was expressed under control of either the promoter of the small subunit of ribulose 1,5-bisphosphate carboxylase (rbcS promoter; lines 2, 9 and 18) or the 35S promoter from cauliflower mosaic virus (CaMV promoter; line 13). The rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 38 publications
6
56
1
1
Order By: Relevance
“…Galtier et al (1993) demonstrated a positive relationship between SPS activity and the sucrose/starch ratio by changing the level of SPS in tomato transformed with a maize SPS gene, resulting in increased starch degradation in the chloroplasts. Similar effects were reported by Galtier et al (1995) and Micallef et al (1995). Thus, once dihydroxyacetone phosphate (DHAP) is released from the chloroplast, the rate of sucrose synthesis is regulated by SPS activity.…”
Section: Introductionsupporting
confidence: 69%
“…Galtier et al (1993) demonstrated a positive relationship between SPS activity and the sucrose/starch ratio by changing the level of SPS in tomato transformed with a maize SPS gene, resulting in increased starch degradation in the chloroplasts. Similar effects were reported by Galtier et al (1995) and Micallef et al (1995). Thus, once dihydroxyacetone phosphate (DHAP) is released from the chloroplast, the rate of sucrose synthesis is regulated by SPS activity.…”
Section: Introductionsupporting
confidence: 69%
“…In transgenic tomato overexpressing a maize SPS gene and wild-type tomato under ambient [C0 2 ], no significant difference was observed in estimated carbohydrate export from the source leaves (Galtier et al, 1995), and under elevated [C0 2 ], the export rate was only slightly (5%) higher in transgenic tomato (Murchie et al, Galtier et al, 1995;Murchie et al, 1999). In tomato, starch might accumulate to a level that exceeds the demand, and other regulatory mechanisms, such as activity of the sucrose transporter, might counteract the advantage of the high SPS activity under elevated [C0 2 ], as mentioned by Murchie et al (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf samples were Lyophilised in a freeze dryer (Labconco Freezone18). The freeze dried leaf materials (5 g) were homogenised in 1M HClO 4 (25 ml), and the extract was centrifuged at 12,000 g for 5 min at 4 o C (Galtier et al, 1995).…”
Section: Methodsmentioning
confidence: 99%